1991
DOI: 10.1128/jb.173.2.860-868.1991
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and analysis of dominant secA mutations in Escherichia coli

Abstract: The secA gene product is an autoregulated, membrane-associated ATPase which catalyzes protein export across the Escherichia coli plasma membrane. Previous genetic selective strategies have yielded secA mutations at a limited number of sites. In order to define additional regions of the SecA protein that are important in its biological function, we mutagenized a plasmid-encoded copy of the secA gene to create small internal deletions or duplications marked by an oligonucleotide linker. The mutagenized plasmids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
1
24
0
2
Order By: Relevance
“…Finally, strains with secretion-defective secA alleles had very high ␤-galactosidase activities, particularly after IPTG induction. This pattern is reminiscent of our previous work, where secretion-defective secA alleles caused dominant protein secretion defects and secA derepression due to subunit mixing and "poisoning" of the SecA homodimer (55).…”
Section: Fig 3 Atp-dependent Helicase Activity Of Seca Proteinsupporting
confidence: 50%
“…Finally, strains with secretion-defective secA alleles had very high ␤-galactosidase activities, particularly after IPTG induction. This pattern is reminiscent of our previous work, where secretion-defective secA alleles caused dominant protein secretion defects and secA derepression due to subunit mixing and "poisoning" of the SecA homodimer (55).…”
Section: Fig 3 Atp-dependent Helicase Activity Of Seca Proteinsupporting
confidence: 50%
“…1C). Six of the mutants (secAL785R, secAI789R, secAP799A, secAE802A, secAY803A, and secAE806A) were barely viable, as was partial deletion of IRA1 (secA⌬783-795) (15,30). Three mutants (secAW775A, secAF811A, and secAR792A) complemented the thermosensitive strain, albeit not as efficiently as secA.…”
Section: Ira1 Mutationsmentioning
confidence: 99%
“…Oligohistidinyl-tagged SecA IRA1 mutants were purified and shown, like SecA⌬783-795 (15,30), to be stable, folded, and ␣-helical (far UV CD; data not shown) and dimeric (size exclusion chromatography, blue native PAGE, sedimentation equilibrium; data not shown). We concluded that IRA1 mutant proteins do not have significantly altered structures and were characterized biochemically.…”
Section: Ira1 Mutationsmentioning
confidence: 99%
“…his 10 -secA⌬351-368 was constructed by subcloning the 2.5-kb NcoI fragment from pGJ5 (13) to the corresponding site of pIMBB7, resulting in pIMBB83.…”
Section: Methodsmentioning
confidence: 99%
“…DEAD motors acquire specificity for different catalytic processes through add-on nonhomologous structural appendages (8,11). SecA has two such structures (12)(13)(14) (Fig. 1, A and B): (a) the C-domain (aa 611-832), which is fused C-terminally to the IRA2 domain of the DEAD motor and regulates its mobility and properties by "stapling" together NBD and IRA2 (14,15), and (b) a second appendage (aa 221-377) of unknown function, which forms an independent structural domain ( Fig.…”
mentioning
confidence: 99%